A micro-mechanics based viscoplastic model for clayey rocks. (September 2017) - Farhat, F.; Shen, W.Q.; Shao, J.F.
Abstract: In this study, a micro-mechanics based viscoplastic model is proposed to describe time-dependent deformation for a class of clayey rocks. The heterogeneous rock is represented as a composite material containing a porous clay matrix and mineral inclusions at a mesoscopic scale. The clay matrix is composed of a solid phase and pores at the microscopic scale. The effective plastic yield criterion is determined from a nonlinear homogenization procedure (Shen et al., 2013). This criterion is extended and used as a viscoplastic loading function. Together with a suitable hardening law and a non-associated flow rule, the viscoplastic model is completed. A series of numerical assessments are presented to investigate the influence of porosity and mineral inclusions on the time-dependent deformation of clayey rocks. Comparisons between numerical results and experimental data are also performed and presented for different loading paths.